SISTEM AKAD TRANSAKSI JUAL BELI ONLINE DROPSHIPPING PERSPEKTIF MAQASHID SYARI’AH - Sahnaz Kartika Harahap; Dhiauddin Tanjung (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
In knowledge of Islam, buying and selling must be in accordance with Islamic law. Dropshipping is the practice of buying and selling transactions carried out online. In terms of the dropshipping system, this is defined as buying and selling where the seller does not have stock of merchandise and then the buyer places an order and pays in advance. After receiving an order from the buyer, then the order is submitted to the supplier and then the supplier will send the ordered goods directly to the customer but with the name dropshipper. This dropshipping sale and purchase has caused a lot of polemic regarding the validity of the transaction and its legal status. The purpose of this study is to find out how the dropshipping online buying and selling transaction contract system is then viewed from the maqashid shari'ah perspective. This study uses qualitative research methods with descriptive analysis based on literature studies. From the results of the study, it can be concluded that online buying and selling transactions using the dropshipping system are not prohibited in Islam and can be used with several contracts such as salam contracts, wakalah contracts, and also samsarah contracts. In practice, dropshipping must be in accordance with maqashid sharia which aims to benefit.